2021
DOI: 10.1371/journal.pone.0245037
|View full text |Cite|
|
Sign up to set email alerts
|

Phylogenetic diversity, trichothecene potential, and pathogenicity within Fusarium sambucinum species complex

Abstract: The Fusarium sambucinum species complex (FSAMSC) is one of the most taxonomically challenging groups of fusaria, comprising prominent mycotoxigenic plant pathogens and other species with various lifestyles. Among toxins produced by members of the FSAMSC, trichothecenes pose the most significant threat to public health. Herein a global collection of 171 strains, originating from diverse hosts or substrates, were selected to represent FSAMSC diversity. This strain collection was used to assess their species dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 103 publications
4
53
0
3
Order By: Relevance
“…The first phase was characterized by the discovery that the morphospecies F. graminearum comprises at least 16 phylogenetic species, and development of tools to facilitate identification of these species and of their trichothecene genotypes. It should be noted that four species basal to the FGSC, in what is now recognized as the Graminearum Clade (Laraba et al 2021), were discovered and described during roughly the same period. These included F. pseudograminearum, which was previously reported as the Group 1 population of F. graminearum (Aoki and O'Donnell 1999), F. dactylidis from orchard grass in Oregon and New Zealand (Aoki et al 2015), F. praegraminearum from maize field litter in New Zealand (Gräfenhan et al 2016), and F. subtropicale from barley in Brazil (Pereira et al 2018).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The first phase was characterized by the discovery that the morphospecies F. graminearum comprises at least 16 phylogenetic species, and development of tools to facilitate identification of these species and of their trichothecene genotypes. It should be noted that four species basal to the FGSC, in what is now recognized as the Graminearum Clade (Laraba et al 2021), were discovered and described during roughly the same period. These included F. pseudograminearum, which was previously reported as the Group 1 population of F. graminearum (Aoki and O'Donnell 1999), F. dactylidis from orchard grass in Oregon and New Zealand (Aoki et al 2015), F. praegraminearum from maize field litter in New Zealand (Gräfenhan et al 2016), and F. subtropicale from barley in Brazil (Pereira et al 2018).…”
Section: Discussionmentioning
confidence: 91%
“…This extensively validated and high-throughput method relies on probes targeting nucleotide variation within multiple genes to simultaneously determine the species identity and trichothecene chemotype of isolates (Ward et al 2008). The MLGT method has also enabled the discovery of novel FGSC and F. graminearum Clade species (sensu Laraba et al 2021) and interspecific hybrids (Boutigny et al 2011(Boutigny et al , 2014Pereira et al 2018;Sarver et al 2011). A smaller number of studies have employed fragment analysis of polymorphic markers (RFLP, AFLP or ISSR; n = 1,686; 10.3%), and polymerase chain reaction (PCR) with species-specific primers (e.g.…”
Section: Methodology For Species and Chemotype Identificationmentioning
confidence: 99%
“…In particular, both F. equiseti , a member of FIESC, and F. brachygibbosum , proved to be moderately pathogen in Qatar, in a date palm detached leaf assay [ 16 ], while F. brachygibbosum was reported to be a weak pathogen of roots in Oman [ 13 ]. It is important to underline that recent new taxonomic analyses of both FIESC and F. brachygibbosum have generated new phylogenetic species in FIESC [ 35 ] and split F. brachygibbosum in 12 phylogenetic new species grouped in F. brachygibbosum clade within FSAMSC [ 36 ]. Therefore, the different pathogenicity on date palm shown by FIESC members and F. brachygibbosum in different assays, reported in different papers, can be due to different phylogenetic species tested.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the production of type B trichothecenes fusarenon X and 4,15diacetoxy-nivalenol by F. brachygibbosum isolated from legume pastures in Australia [ 56 ] and soybean roots in Ethiopia [ 57 ]. On the other hand, more recently, Laraba et al [ 36 ] reported that strains of F. brachygibbosum isolated from Virgin jungle soil in Thailand and pearl millet in Niger could produce the type A trichothecenes diacetoxyscirpenol and neosolaniol. Our report is consistent with Laraba et al [ 36 ], since DAS and NEO are well-known precursors of T-2 and HT-2 type A trichothecenes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation